2020
DOI: 10.1080/19491034.2020.1798093
|View full text |Cite
|
Sign up to set email alerts
|

Exportins can inhibit major mitotic assembly events in vitro: membrane fusion, nuclear pore formation, and spindle assembly

Abstract: Xenopus egg extracts are a powerful in vitro tool for studying complex biological processes, including nuclear reconstitution, nuclear membrane and pore assembly, and spindle assembly. Extracts have been further used to demonstrate a moonlighting regulatory role for nuclear import receptors or importins on these cell cycle assembly events. Here we show that exportins can also play a role in these events. Addition of Crm1, Exportin-t, or Exportin-5 decreased nuclear pore assembly in vitro. RanQ69L-GTP, a consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…3a and Supplementary Fig. 7), we conducted immunostaining of nuclear pore complexes (NPCs) using NPC antibodies (mAb414) [27,28]. GUVs containing a nucleus-like structure were fixed with 2.0% glutaraldehyde and stained with mAb414-Alexa Fluor 594 (mAb414-AF594; see 'Methods' for the details on immunostaining).…”
Section: Immunostaining Of Nuclear Pore Complexes On Nuclear Membranementioning
confidence: 99%
“…3a and Supplementary Fig. 7), we conducted immunostaining of nuclear pore complexes (NPCs) using NPC antibodies (mAb414) [27,28]. GUVs containing a nucleus-like structure were fixed with 2.0% glutaraldehyde and stained with mAb414-Alexa Fluor 594 (mAb414-AF594; see 'Methods' for the details on immunostaining).…”
Section: Immunostaining Of Nuclear Pore Complexes On Nuclear Membranementioning
confidence: 99%
“…21,22 Although the mitotic roles of XPO1 are poorly characterized relative to those of KPNB1, recent literature by Nord et al illustrates that XPO1, in concert with Exportin 5 and Exportin T, has similar inhibitory effects on major mitotic events, such as membrane fusion and nuclear pore formation via interactions with various nucleoporins and RanGTP-dependent mechanism. 23 Nuclear receptors globally control the distribution of proteins across the nuclear membrane. Given the extent to which spatiotemporal localization dictates the activity of both receptor and cargo, it is not surprising that aberrant functioning of the nuclear transport machinery is associated with pathogenic disease states, such as cancer.…”
Section: The Nuclear Transport Systemmentioning
confidence: 99%
“…Phosphorylation of XPO1 serine 391 by CDK1‐cyclin B promotes the transfer of sequestered RanBP1 from KPNB1 to XPO1, thereby facilitating RanBP1 localization to kinetochores, an event which is crucial for kinetochore function after chromosomal attachment 21,22 . Although the mitotic roles of XPO1 are poorly characterized relative to those of KPNB1, recent literature by Nord et al illustrates that XPO1, in concert with Exportin 5 and Exportin T, has similar inhibitory effects on major mitotic events, such as membrane fusion and nuclear pore formation via interactions with various nucleoporins and RanGTP‐dependent mechanism 23 …”
Section: The Nuclear Transport Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear pore complexes (NPCs) are large macromolecular complexes embedded in the nuclear membrane that control the bidirectional molecular transport channels between cytoplasm and nucleus 9 , 10 . NPCs are composed of a variety of nucleoporins (NUPs), including NUP160, NUP155, and NUP85 11 , 12 . More and more evidences have confirmed that NUPs are related to lipid metabolism and inflammation of liver diseases 13 .…”
Section: Introductionmentioning
confidence: 99%